Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jpowsour.2015.03.087
|View full text |Cite
|
Sign up to set email alerts
|

Na0.44MnO2 with very fast sodium diffusion and stable cycling synthesized via polyvinylpyrrolidone-combustion method

Abstract: h i g h l i g h t s g r a p h i c a l a b s t r a c t At 20C, the capacity remains 99 mAh g À1 which is over 80% of that at C/5. The chemical diffusion coefficient of sodium is around 3 Â 10 À12 cm 2 s À1 . The capacity retention at 10C after 700 cycles is 82.9% and the coulombic efficiency keeps near 99.8%. a b s t r a c t Na 0.44 MnO 2 is a very promising cathode material in sodium-ion batteries for large-scale application. Na 0.44 MnO 2 with very fast sodium diffusion and stable cycling is prepared by polyv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 59 publications
(39 reference statements)
2
62
0
Order By: Relevance
“…Later, Liu and co‐workers investigated the effect of calcination temperature on the electrochemical performance of Na 0.44 MnO 2 and found that 900 °C is the optimal annealing condition. The obtained Na 0.44 MnO 2 nanowire has a longer length and a smaller width than the control samples, battery tests showed that the cathode delivered a capacity of 99 mAh g −1 at 20 C . Recently, a symmetric sodium‐ion capacitor based on Na 0.44 MnO 2 with high power was also reported .…”
Section: Cathode Materialsmentioning
confidence: 95%
See 1 more Smart Citation
“…Later, Liu and co‐workers investigated the effect of calcination temperature on the electrochemical performance of Na 0.44 MnO 2 and found that 900 °C is the optimal annealing condition. The obtained Na 0.44 MnO 2 nanowire has a longer length and a smaller width than the control samples, battery tests showed that the cathode delivered a capacity of 99 mAh g −1 at 20 C . Recently, a symmetric sodium‐ion capacitor based on Na 0.44 MnO 2 with high power was also reported .…”
Section: Cathode Materialsmentioning
confidence: 95%
“…In its crystal structure, sodium ions can be located in wide S‐shaped and narrower tunnels. It is expected that only the large S‐shaped tunnels can offer diffusion path to accommodate the relatively large size of sodium ions ( Figure a,b), therefore, the x of tunnel Na x MnO 2 varies over the range of 0.22–0.66 during charge and discharge process with a series of phase changes (Figure c) …”
Section: Cathode Materialsmentioning
confidence: 99%
“…For example, MnO 2 have been widely used as electrode materials in supercapacitors . Na x MnO 2 is a kind of attractive battery‐type cathode material for NIBs, i.e., Na 0.44 MnO 2 , as shown in Figure a, because of its large‐size tunnels into which Na + can be readily inserted . Gogotsi and co‐workers fabricated a device using Ti 3 C 2 MXene/CNT composite as anode and Na 0.44 MnO 2 as cathode, which delivered a volumetric discharge capacity of 286 mAh cm −3 , based on the volume of anode electrodes, as shown in Figure b .…”
Section: Materials For Sodium‐ion Capacitorsmentioning
confidence: 99%
“…d) Charge–discharge curves and e) rate performance of NIC with VO 2 anode and NVP cathode (VO 2 //NVP) at different current densities. a) Reproduced with permission . Copyright 2015, Elsevier B.V. b) Reproduced with permission .…”
Section: Materials For Sodium‐ion Capacitorsmentioning
confidence: 99%
“…More recently, NMO materials have also been prepared by other synthesis procedures such as wet-chemistry techniques [12], including modified-Pechini methods [16][17][18], spray pyrolysis [19], polyvinilpyrrolidone (PVP)-assisted gel combustion synthesis [20,21], and reverse microemulsion methods [22,23]. However, even if a solution precursor is used, the NMO materials are usually obtained at high temperatures between 800 • C [12,17,18] and 950 • C [16,20,21] after several hours of annealing, typically ranging between 8 and 15 h. Notable exceptions are related to hydrothermal preparation strategies, where typically an aqueous solution is heated at only 205 • C, but for 4 days, in an autoclave [24,25]. Quite surprisingly, NMO materials deliver similar electrochemical performance and specific capacities at low current rates (i.e., approaching the theoretical capacity of 121 mA h g −1 ), despite being synthesized via different methodologies.…”
Section: Introductionmentioning
confidence: 99%